The influence of disinfection on dimensional stability of temporary crowns - de Carvalho, Paula Carolina Komori [UNESP]; de Almeida, Lais Medeiros Ribeiro [UNESP]; Sacourague, Sâmia Carolina Mota Cavalcanti [UNESP]; Kimpara, Estevão Tomomitsu [UNESP]; Paes Junior, Tarcisio José de Arruda [UNESP] (Editora Cubo, 2018)
Objective: Evaluate the influence of different disinfection methods on the dimensional stability of temporary acrylic resin crowns. Material and Methods: A metallic die with two different marks at the margin was used to prepare the specimens with two different resins (bis-acrylic resin-Structur, acrylic resin-Dencrilay). They were divided into eight groups (n=8), determined according to the disinfection methods (microwave, acetic acid, 1% hypochlorite) and control. The marginal adaptation was recorded using an optical microscope (50X) comparing two different marks on the margin of the crowns with 2 points along the entire circumferential margin before and after disinfection methods. Results: Results were compared statistically by ANOVA and Tukey’s test (p≤0.05). The two-way ANOVA showed statistical difference between types of materials. No significant differences were found between disinfection methods and interaction of factors. Conclusion: All procedures affected the marginal adaptation however temporary crowns made by bis-acrylic resin demonstrate higher dimensional stability.
A influência da desinfecção na estabilidade dimensional de coroas temporárias
Keywords: Dimensional stability; Disinfection; Temporary crowns